2022
DOI: 10.1002/ajoc.202200616
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Molecular Iodine Catalyzed/Mediated Multicomponent Reactions

Abstract: In multicomponent reactions, three or more reactants combine in one pot to form a product without the isolation of intermediate and most of the reactants contribute to newly formed product reducing number of steps involved and waste generated. Molecular iodine is mild, efficient, relatively nontoxic, inexpensive, commercially available, and catalyzes various organic reactions due to its Lewis acidic behaviour. The development of multicomponent reactions catalyzed by molecular iodine indeed is a good green alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 186 publications
0
10
0
Order By: Relevance
“…The anti-inflammatory activity of benzimidazole derivatives has been reported through several research studies. 43,44 However, the benzimidazole molecules (Figure 8, 24-26) discussed in this section are those that have shown good anti-inflammatory properties in the work of Monika Gaba et al 45 In this study, the anti-inflammatory activities of the molecules were compared with those of reference drugs such as Indomethacin, Nimesulide, Ibuprofen and Diclofenac. These benzimidazole derivatives showed activity above that of the reference drugs.…”
Section: F Anti-inflammatory Properties Of Benzimidazole Derivativesmentioning
confidence: 99%
“…The anti-inflammatory activity of benzimidazole derivatives has been reported through several research studies. 43,44 However, the benzimidazole molecules (Figure 8, 24-26) discussed in this section are those that have shown good anti-inflammatory properties in the work of Monika Gaba et al 45 In this study, the anti-inflammatory activities of the molecules were compared with those of reference drugs such as Indomethacin, Nimesulide, Ibuprofen and Diclofenac. These benzimidazole derivatives showed activity above that of the reference drugs.…”
Section: F Anti-inflammatory Properties Of Benzimidazole Derivativesmentioning
confidence: 99%
“…18 Very recently, Monika et al have reported a review article, which focuses mainly on the role of molecular iodine in multicomponent reactions. 23 In 2020, Latha et al 24 reported a review article, which describes the functionalization methods of methylazaarenes. However, to the best of our knowledge, there is no such literature available that specifically focuses on the iodine-DMSO mediated C(sp 3 )-H functionalization via Kornblum oxidation.…”
Section: Kornblum Oxidationmentioning
confidence: 99%
“…In order to meet the above-mentioned requirements, the combination of I 2 /DMSO as a catalyst and solvent has emerged as a versatile approach. 1,2 Molecular iodine (I 2 ) has gained signicant popularity as a catalyst and reagent due to its notable attributes, [3][4][5] including its cost-effectiveness as an alternative to transition and rare earth metals, its environmentally friendly nature, non-toxicity, high stability, low sensitivity to moisture, ease of handling, and notably its exceptional performance across a wide range of reaction mixtures, including highly concentrated and solvent-free systems. 6 Collectively, these characteristics make I 2 a versatile and unique catalyst and reagent.…”
Section: Introductionmentioning
confidence: 99%